Análise da lei 10.639/03: uma revisão da literatura acerca dos desafios da implementação, dos avanços no ensino de história e das perspectivas futuras para a educação étnico-racial - FERNANDES, Joelma Sinara Araújo (Universidade Federal do Oeste do Pará, 2024)
This article has the purpose of analyzing the contributions of Law 10.639 / 03 to the Teaching of History, in the sense of rediscussing the challenges, advances, ruptures and future perspectives, in the context of education for ethnic-racial relations. The methodological proposal was the literature review, the bibliographic research and the case study. Based on these assumptions, it is stated that it was to curb the systematic reproduction and advancement of policies of inequalities with black and Afro-descendant Brazilians. The Black Movement since the 1960s intensified the march and the cry for Affirmative Actions. principal exponent the implementation of an innovative legislation that so the promulgation of Law 10.639 / 03. Thus, this article revisits this approach to law and its reflexes in Teaching History in these almost fifteen years, from an intercultural perspective based on the process of decolonization of the school and the curriculum, historically reproduced from the Eurocentric.